Simplified method for evaluating the response of existing tunnel induced by adjacent excavation. (27th October 2022) - Feng, Guohui; Xu, Changjie; Liang, Luju; Tey, Ming‐wang; Chi, Min‐liang; Ge, Shangqi
Abstract: Adjacent excavation may have a negative influence on the existing tunnel underneath. Thus, it is important to evaluate the response of the tunnel due to adjacent excavation. However, there is little report about using the Kerr foundation model to simulate the tunnel‐soil interaction. Meanwhile, the Timoshenko beam, which can take the tunnel shearing effect into consideration, is more suitable to estimate the behavior of the tunnel. To simulate the interaction between soil and tunnel, the existing tunnel is simplified as a Timoshenko beam lying on the Kerr foundation model, and a simplified theoretical method is proposed to calculate the response of the existing tunnel induced by adjacent excavation. The proposed method is validated by two field case studies. Results indicate that the predictions given by the proposed method show great agreement with field measurements and it is more accurate to evaluate the tunnel‐soil interaction compared with the previous method. The further parametric study shows that the relative position between excavation and tunnel, the ground Young's modulus, the depth of existing tunnel centerline, and length and width of excavation are both significant factors governing the tunnel response induced by adjacent excavation, while the influence of tunnel shear stiffness and skew between tunnel and excavation are slight. The proposed method can be applied to predict the potential risk of existing tunnels induced by adjacent excavation in relevant engineering projects.